2017
DOI: 10.1063/1.4973327
|View full text |Cite
|
Sign up to set email alerts
|

Scalar transport in inline mixers with spatially periodic flows

Abstract: Spatially persisting patterns form during the downstream evolution of passive scalars in three-dimensional (3D) spatially periodic flows due to the coupled effect of stretching and folding mechanisms of the flow field. This has been investigated in many computational and theoretical studies of 2D time-periodic and 3D spatially periodic flow fields. However, experimental studies, to date, have mainly focused on flow visualization with streaks of dye rather than fully 3D scalar field measurements. Our study empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…A satisfactory agreement is also obseved between our predicted results and the correlation of Grace [21].…”
Section: Validation Of Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…A satisfactory agreement is also obseved between our predicted results and the correlation of Grace [21].…”
Section: Validation Of Resultssupporting
confidence: 87%
“…In this paper, we studied the influence of Reynolds number, fluid viscosity, aspect ratio and the number of helical elements on the flow patterns and pressure drop. It was found that the CFD results of pressure drop were similar to the literature data (the numerical simulation of Saatdjian et al (2012) and the correlation of Grace (1971)).…”
Section: Numerical Study Of Viscous Fluid Flows In a Kenics Static Mixersupporting
confidence: 82%
See 1 more Smart Citation
“…Here the transverse flow is driven by viscous drag exerted by a rotating outer cylinder via apertures in the stationary inner cylinder (Fig. 6(a)); the cell-wise reorientation angle Θ following (10) is the angular offset of consecutive apertures accomplishes systematic 8 Flow in such devices normally settles on a repeated pattern and thus effectively becomes periodic after a short transient following the inlet [84]. The RAM is inspired by the Partitioned-Pipe Mixer (PPM) shown in Fig.…”
Section: Industrial and Technological Relevancementioning
confidence: 99%
“…Fig. 11 demonstrates the transverse mixing within each duct segment by horizontal and vertical splitting (and subsequent recombination) of the axial throughflow by the central plates of elements 1 and 2, respectively, via the 3D streamline pattern measured with 3D Particle Tracking Velocimetry (3DPTV) [94,84]. Mixing element 1 splits the incoming fluid into two separate streams (indicated in red and green) that, in turn, undergo further splitting by element 2, resulting in a "mixture" of red and green streamlines at the segment exit.…”
Section: Generic Flow Topologymentioning
confidence: 99%